Poverty Reduction in Sub-Saharan Africa: A Call for Financial Inclusion - Malekano, Shamiso (University of Cape Town, 2021)
This dissertation proposes an Index of Financial Inclusion (IFI) for Sub-Saharan Africa and then uses the developed index to investigate the significance of the relationship between financial inclusion and economic development and growth. This is important because there is no consensus in the literature on how to measure financial inclusion or on the direction of the causal relationship between financial inclusion and economic development or growth. This dissertation aims to contribute to these two debates whilst focusing on Sub-Saharan Africa, where development (potentially encouraged by financial inclusion) is desperately needed. The IFI for Sub-Saharan Africa is arrived at by first determining those dimensions of financial inclusion that are important for the countries in the region. This was done through a text analysis of National Financial Inclusion Strategies (NFISs) of 13 Sub- Saharan African countries overlaid on a detailed literature review. Access, Usage and Quality are the key dimensions for measuring levels of financial inclusion in the region. Thereafter, appropriate variables for the measurement of those dimensions were identified and combined using different methodologies: the simple geometric mean method, the inverse Euclidean distance method and, lastly, the factor analysis method. The relationship between the developed index and economic development and growth is tested using correlations and regression analyses. It was demonstrated that the IFI fits the NFISs of Sub-Saharan African countries and is practically executable. This implies that the IFI is perhaps more appropriate to be used in the region than the global measures previously proposed. Weak correlations between the IFI and economic development or growth were found. These last tests were hampered by small sample sizes and thus the causation debate, mentioned in the motivation paragraph, could not be resolved. However, the proposed IFI for Sub- Saharan Africa shows potential.